Mekong Delta master plan (VIE/87/031) : (Netherlands Engineering Consultants, 1992)
Contents: Mekong Delta land elevation, Mekong Delta water levels, Mekong Delta salt intrusion, Mekong Delta tidal irrigation and drainage...